Senegal : Third Review Under the Policy Coordination Instrument and Request for Modification of Quantitative Targets, and Requests for a Stand-By Arrangement and an Arrangement Under the Standby Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2021)
The macroeconomic outlook has worsened amid a second wave of the COVID-19 pandemic, higher commodity prices and social unrest, rooted in widening inequality and a lack of opportunities for the youth. The COVID-19 vaccination campaign was launched in February but has so far covered less than 5 percent of Senegal's population. The President announced in early April an emergency program for youth employment and economic insertion amounting to 3 percent of GDP, spread evenly over 2021-23.